Description of Satisfaction Level of BPJS Health Denture Patients in Dental Hospital of South Sumatera Province - Rafidah Syifa Muthi’ah; Sri Wahyuningsih Rais; Bertha Aulia (Dentistry Study Program, Faculty of Medicine Universitas Sriwijaya, 2021)
Introduction: Dental Hospital of South Sumatera Province is a government hospital that has collaborated with BPJS Health since 2016. One of the health services provided is prosthodontic treatments. Purpose: The purpose of this study was to determine the satisfaction level of BPJS Health denture patients in Dental Hospital based on five service dimensions, i.e tangible, reliability, responsiveness, assurance, and empathy. Method: This study was a descriptive survey with a cross-sectional design and using total sampling technique. The subjects were all BPJS Health denture patients in the Dental Hospital of South Sumatera Province in 2018, involving total 51 participants. Data was obtained by using a measuring instrument in the form of a questionnaire. Results: Respondents were satisfied based on the dimensions of tangible, reliability, responsiveness, assurance, and empathy 100%, 74%, 89%, 81%, and 94% respectively. Conclusion: BPJS Health denture patients were satisfied with dental and oral health services at the Dental Hospital of South Sumatera Province.